Proteomics and Food Analysis: Principles, Techniques, and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book, Proteomics and Food Analysis: Principles, Techniques, and Applications, edited by Dr. Mónica Carrera and published by MDPI, is an excellent collection of a wide range of proteomics approaches applied in food analysis.